Peace Education: A Tool for Resolving Direct and Structural Violence Against Teachers in Lukulu District (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This phenomenological study explores the lived experiences of teachers affected by direct and structural violence in the divided community of Lukulu district of the Western Province of Zambia. The objectives of this study were to; explore teachers' experiences of direct and structural violence in some selected schools of Lukulu district, investigate the causes of direct and structural violence against teachers as well as provide recommendations for resolving direct and structural violence against teachers in Lukulu district. The study was guided by the structural violence theory (Galtung, 1969), Peace education theory (Harris, 2003) and the Critical Peace education theory (Wulf,1974). The study employed interpretive phenomenological analysis, thereby interviewing fifteen participants in the categories of five school managers and ten teachers from five purposively sampled schools.Thematic analysis was used to interpret the findings and investigate the ways in which division, direct and structural violence against teachers affected the delivery of education, development and welfare of teachers. The study revealed that structural violence against teachers manifested in verbal abuse of teachers by senior managers, direct political violence on the teachers perceived to belong to other political parties by the ruling party cadres, violence in form of insults from pupils, parents and community members and chronic gossiping and rumour mongering which proved to be detrimental to the wellbeing of the teachers. Additionally, the study highlighted some of the causes of violence against teachers such as political interference in the running of educational institutions, corruption, bribery and favouritism; lack of transparency and accountability in the appointment of teachers to management positions and poor representation and support from respective teacher unions. Besides that, the study revealed several effects of violence against teachers such as physical injuries, loss of human life, suicide, loss of property, closure of schools, loss of teaching and learning time as teachers tend to pursue court cases against perpetrators of the violence. In view of the foregoing, this study recommended implementation of policy reforms that addresses the structural inequalities and peace education such as establishment of the directorate of peace education, development and international education at national, provincial, district and school levels that should have in its structure a national peace education, development and international education director, provincial peace education and development mentors, district peace education and development mentors and school peace education and development mentors. These officers would be critical to advancing the peace education agenda through comparative and international education advocacy. Finally, this study contributes to Galtung (1969)'s concept of positive peace by proposing three forms of positive peace education. These are direct positive peace education, structural positive peace education and cultural positive peace education. These are critical to the resolution of direct, cultural and structural violence against teachers.